Cytokine release syndrome after radiation therapy: case report and review of the literature - Christopher A. Barker; Samuel K. Kim; Sadna Budhu; Konstantina Matsoukas; Anthony F. Daniyan; Sandra P. D’Angelo (Journal for ImmunoTherapy of Cancer, 2018)
Abstract Background Cytokine release syndrome (CRS) has been reported after immunologic manipulations, most often through therapeutic monoclonal antibodies. To our knowledge, CRS after radiation therapy (RT) for cancer has not been reported before. The development of unusual clinical signs and symptoms after RT led us to investigate the possibility of CRS after RT and review the medical literature on this topic. Case presentation A 65 year-old man with untreated chronic lymphocytic leukemia and recurrent, metastatic Merkel cell carcinoma undergoing anti-programmed death 1 (PD1) immunotherapy was referred for palliative RT to sites of progressing metastases. Within hours of each weekly dose of RT, he experienced fever, tachycardia, hypotension, rash, dyspnea, and rigors. Based on clinical suspicion for CRS, blood cytokine measurements were performed 1 h after the second and third dose of RT and demonstrated tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) levels approximately ten-fold higher than normal. These were near normal immediately prior to the third dose of RT, and resolved to normal levels 3 weeks after RT. He experienced rapid regression of irradiated tumors, with development of new sites of metastases soon thereafter. A literature review revealed no clinical cases of CRS after RT for cancer. Conclusions RT during anti-PD1 immunotherapy in a patient with underlying immune dysfunction appeared to be the putative mediator of an immune process which yielded significant increases in pro-inflammatory cytokines, and produced the clinical symptoms meeting the definition of grade 3 CRS. This case demonstrates the capability of RT to elicit immune-related adverse events.